Smoking and Obesity are Risk Factors for Thirty-Day Readmissions Following Skull Base Surgery - Makwana, Milan; Taylor, Peter N.; Stew, Benjamin T.; Shone, Geoffrey; Hayhurst, Caroline (Journal of Neurological Surgery Part B: Skull Base, 2020)
Background Thirty-day readmission has become a significant health care metric reflecting the quality of care and on the cost of service delivery. There is little data on the impact of complications following skull base surgery (SBS) on emergency readmission. Identifying modifiable risk factors for readmission may improve care and reduce cost.Design The study was designed as a single-center retrospective cohort study.Methods Records for a consecutive series of 165 patients who underwent open or endoscopic SBS by a single surgeon reviewed. Patients with pituitary adenoma were excluded. The diagnosis, procedure, complications, length of stay (LOS), body mass index (BMI), and smoking status were recorded. Readmission to the neurosurgical department or regional hospitals was either noted prospectively or the patient contacted. Cause and length of readmission was documented.Results Of the 165 cases, 14 (8.5%) were readmitted within 30 days. Causes for readmission included cerebrospinal fluid (CSF) leak in 5/14 or 35.7% (overall rate for readmission for this complication in the series is 3.1%), infection in 4/14 (28.6%), hyponatraemia in 2/14 (14.3%), vascular: sinus thrombosis in 1/14 (7.1%), seizures in 1/14 (7.1%), and epistaxis in 1/14 (7.1%). Initial and readmission LOS was 6 and 14 days, respectively. BMI was higher in those readmitted within 30 days (33.2 kg/m2) versus no readmission (27.1 kg/m2). In addition, of those readmitted within 30 days, 35.7% were smokers compared with 20.8% in those not readmitted.Conclusion In this series, smoking and raised BMI may be indicators for within 30-day readmission and complications in this population, raising the question of risk factor modification prior to elective intervention.
Keywords: skull base; 30-day readmission; smoking; obesity